Catatan Hukum Kritis Pembiayaan Sekunder Perumahan - Rahmi Jened (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2019)
Abstracthe existence of Secondary Mortgage Facility (SMF) in Indonesia is adopted from common law s tradition. It is not easy to adopt legal institutions derived from the common law tradition into our country that base on the civil law tradition. Furthermore, even though SMF has managed to solve mismatch and improve credit liquidity, hence there are some critical legal notes to SMF institution. This paper will discuss about the differences law and regulation of real property ownership, true sale for repurchase of loan and its   secured transaction (mortgage) and the existence of Special Purpose Vehicle between Common Law and civil Law tradition. IntisariEksistensi lembaga Fasilitas PembiayaanSekunder Perumahan (SMF) di Indonesia diadopsi dari common law system. Tentu bukan hal mudah untuk mengadopsi lembaga hukum dari tradisi common law ke dalam tradisi civil law. Meskipun telah terbukti lembaga ini dapat mengatasi mismatch dan meningkatkan likuiditas KPR, namun ada beberapa catatan hokum kritis tentang Pembiayaan Sekunder Perumahan.Makalah ini akan membahas perbedaan hokum dan aturan tentang kepemilikan tanah, jual putus untuk penjualan kredit dan hak tanggungannya serta eksistensi perusahaan kendaraan untuk tujuan khusus antara tradisi Common Law dan Civil Law.